Faktor yang Mempengaruhi Fee Based Income Pada Kelompok Bank Berdasarkan Modal Inti (KBMI) 4 - Sugiyarti, Listya; Sutandijo, Sutandijo; Fatiha, Verenika Hafiza (Kompartemen : Jurnal Ilmiah Akuntansi, 2023)
This study aims to determine the effect of third-party funds, electronic banking and foreign exchange transactions on fee-based income at KBMI 4 banks. This type of research is quantitative research with a period of 4 years (Quarterly). Data comes from quarterly financial reports and banking company performance presentation reports with saturated sampling technique. Total samples is 4 bank with 56 observation data. Data analysis used panel data regression analysis with the fixed effect model selected and data testing tool using the Eviews version 12 application. The results obtained in this study were third-party funds, electronic banking and foreign exchange transactions affect fee-based income simultaneously. Third-party funds have no effect on fee-based income with a negative direction, electronic banking has an influence on fee-based income with a positive direction, foreign exchange transactions have an influence on fee-based income with a negative direction.